Indigenous Knowledge and Values in Planning for Sustainable Forestry: Pikangikum First Nation and the Whitefeather Forest Initiative - R. Michael O'Flaherty; Iain J. Davidson-Hunt; Micheline Manseau (Ecology and Society, 2008)
Although still posing challenges, science-based knowledge (including interdisciplinary work) is leading current forest-management planning. How then can indigenous communities mobilize their own knowledge to support their desire to develop new ways of managing the forest? In northern Ontario, the provincial government has developed a cross-scale planning approach that allocates certain responsibilities to First Nations in order to support their vision and knowledge, yet at the same time addresses provincial planning goals.